Atypical COVID-19 dynamics in a patient with mantle cell lymphoma exposed to rituximab - Marcacci, Gianpaolo; Fiorentino, Giuseppe; Volzone, Francesco; Falcone, Umberto; Parrella, Roberto; Donnarumma, Daniela; D’Ovidio, Silvia; Annunziata, Anna; Micallo, Giovanni; Portella, Giuseppe; De Chiara, Annarosaria; De Filippi, Rosaria; et al. (Infectious agents and cancer, 2021)
Patients with non-hodgkin lymphomas (NHL) represent a population of special interest during the current Coronavirus disease-19 (COVID-19) pandemics. NHLs are associated with disease- and treatment-related immunodeficiencies which may generate unusual COVID-19 dynamics and pose unique management challenges. We report the unusual clinical course of COVID-19 in a patient with mantle cell lymphoma (MCL) exposed to nine doses of Rituximab shortly before infection with severe acute respiratory syndrome corona virus 2 (SARS-CoV-2). He had a prolonged asymptomatic phase, with negative molecular and antibody testing for SARS-CoV-2, followed by a rapidly progressive evolution to severe COVID-19. Despite detection of viral RNA overlapped with first symptoms occurrence, anti-SARS-CoV-2 antibodies displayed an asynchronous pattern, with IgG first appearing 2 days after RNA positivity and IgM never being detected throughout the entire clinical course. While disease-associated immune derangements and/or previous treatments involving anti-CD20 antibodies might have contributed to COVID-19 dynamics in our patient, data suggests that antibody testings, without concurrent molecular assessment for SARS-CoV-2, may turn inadequate for monitoring of MCL patients, and in general NHL patients heavily exposed to anti-CD20 antibodies, during the current pandemics. We suggest that repeated molecular testing of nasopharyngeal swab should be implemented in these subjects despite a negative serology and absence of symptoms of SARS-CoV-2 infection. For the same reasons, a customized strategy needs to be developed for patients exposed to anti-CD20 antibodies, based on different features and mechanism of action of available SARS-CoV-2 vaccines and novel vaccinomics developments.